Food Industries for People and Planet: Toward a new research agenda: Summary report of the roundtable and research day June 25-26, 2018 - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
On June 25-26, 2018, over 50 participants representing public and private sector institutions, international organizations, and academia gathered at the International Food Policy Research Institute (IFPRI) headquarters in Washington, D.C. to discuss the priorities and strategic vision for a new research program on Food Industries for People and Planet (FIPP). The discussions resulted in clearer vision for the direction of the program, as well as the identification of several important areas of focus moving forward. This note briefly summarizes the key elements of the discussions and conclusions from both the Roundtable event, held on June 25, 2018, and the Research Day, held on June 26, 2018. The Annexes include the agendas (Annex 1) and participants for both events (Annex 2), as well as a description of the Research Consortium that participants agreed to set up as a key outcome of the Roundtable (Annex 3).